ADSORPTION PROPERTIES OF NANOPOROUS CARBON MATERIALS OBTAINED BY ALKALINE ACTIVATION WITH THERMAL SHOCK - САБЄРОВА, В. О.; ТАМАРКІНА, Ю. В.; РЕДЬКО, А. В.; КУЧЕРЕНКО, В. О. (Technologies and Engineering, 2024)
Purpose. Investigation of the adsorption activity of nanoporous carbon materials (NCMs) prepared by alkali activation with thermal shock. Methodology. The porosity characteristics of NCMs were calculated according to isotherms of low-temperature (77 K) adsorption and desorption of nitrogen (2D-NLDFT-HS method). Adsorption measurements were performed at 25°С and a constant content of NCM (1 g/l) in aqueous solutions. Adsorption kinetics data were calculated by the 1st and 2nd order models and intraparticle diffusion. Adsorption isotherms are approximated by Langmuir and Freundlich models. Findings. It were studied the adsorption kinetics of phenol (Ph), 4-chlorophenol (CPh), methylene blue (MB) and lead cations by NCMs formed from brown coal (NCM(B)) and long-flame coal (NCM(D)) in a new process − alkaline activation with thermal shock. Kinetic data were obtained at the same initial concentration of adsorbates (5.0 mmol/l). The adsorption equilibrium was found to achieve for 2-4 hours depending on the adsorbate. The kinetics of adsorption obeys the second-order equation, and the maximum adsorption capacities increase in the series Pb(II) < MB < Ф < ХФ and are in the range of 0.736–3.350 mmol/g for NCM(B) and 1.097–4.359 mmol/g g for NCM(D). The adsorption rate is limited by the interaction of molecules with surface adsorption centers, and not by diffusion into the NCM nanoporous structure. The initial adsorption rate is highest for the adsorption of CPh (1.672 and 2.050 mmol/g•min), the lowest for the adsorption of MB (0.062 and 0.075 mmol/g•min). During the first minute, about half of the maximum amount of CPh is adsorbed. Adsorption isotherms were found to be approximated by the Langmuir (R2 = 0.981-0.994) and Freundlich (R2 = 0.986-0.998) models with a close errors. The capacities of saturated layers of adsorbates calculated from the Langmuir model increase in the same order as the maximum adsorption capacities. The Freundlich model, which assumes a chemically inhomogeneous adsorbent surface, is better applicable. This is probably a consequence of the fact that the chemical structure of NCM adsorption centers is more diverse due to the «explosive» formation of volatile products during thermal shock. A comparison of the adsorption parameters of the obtained NCMs with literature data allows us to evaluate the synthesized materials as effective adsorbents for purifying aqueous media from pollutants and toxic compounds. Originality. For the first time, the adsorption of phenol, 4-chlorophenol, methylene blue dye and lead cations by NCMs samples formed from brown and long-flame coals under alkaline activation with thermal shock. Practical value. The obtained results make it possible to evaluate the practical prospects of NCMs as adsorption materials for the purification of aquatic environments from ecotoxicants.